Dose-dependent effects of Stevia rebaudiana leaf extract on malondialdehyde and catalase activity in alloxan-induced hyperglycemic rats - Zhira Shada Athaya; Eti Yerizel; Dinda Aprilia; Rozi Abdullah; Fadrian; Westi Permata Wati; Husna Yetti (Acta Biochimica Indonesiana, 2026)
Background: Diabetes mellitus-induced hyperglycemia triggers oxidative stress, characterized by elevated malondialdehyde (MDA) and impaired catalase (CAT) activity. Stevia rebaudiana, rich in steviol glycosides and polyphenols, demonstrates promising antioxidant properties, yet systematic dose-response data on oxidative stress biomarkers remain limited. Objectives: To evaluate the dose-dependent effects of stevia leaf extract on serum MDA levels and CAT activity in alloxan-induced hyperglycemic rats. Methods: Twenty-five male Wistar rats were allocated into normal control, diabetic control (alloxan 120 mg/kg), and three treatment groups receiving alloxan plus stevia extract at 100, 200, or 400 mg/kg body weight orally for 14 days (n=5/group). Serum MDA and CAT were measured spectrophotometrically. Results: Diabetic control showed significantly elevated MDA (2.68±0.62 mg/dL) versus normal control (1.78±0.30 mg/dL). Stevia extract dose-dependently reduced MDA: 1.70±0.19, 1.54±0.20, and 1.38±0.09 mg/dL at 100, 200, and 400 mg/kg, respectively, representing 36.6%, 42.5%, and 48.5% reduction. The 400 mg/kg dose achieved MDA levels comparable to normal control. CAT activity showed dose-dependent restoration trend (7.92±0.76 to 8.58±0.52 mg/dL). Conclusion: Stevia leaf extract (400 mg/kg BW) effectively reduces oxidative stress in hyperglycemic rats through significant dose-dependent MDA reduction, with potential catalase benefits requiring further investigation.